Marcadores moleculares GST e CYP relacionados com fatores clínicos em câncer de mama - Santos, Stéphanie Piacenti dos (2016)
Breast cancer is a leading cause of death in women worldwide. The etiology of this disease is multifactorial, including factors such as habits and lifestyle, hormonal, environmental and genetic. The xenobiotic metabolism contribute to the development of breast carcinoma and polymorphisms in genes encoding enzymes in this pathway, such as GST (GSTM1 and GSTT1) and CYPs (CYP1A1*2A and CYP1A1*2C) have been associated to breast cancer. Objectives: To investigate the influence of the GSTM1, GSTT1, CYP1A1*2A and CYP1A1*2C polymorphisms at the risk for developing breast cancer; to evaluate the association of polymorphisms and risk factors (age, smoking, alcohol, clinical features), tumor clinical and histopathologic features in breast cancer. Methods: This case-control study included 752 women, 219 patients and 533 controls. Molecular analysis were performed by PCR-multiplex (GSTM1 null and GSTT1 null), PCR-RFLP (CYP1A1*2A) and real-time PCR (CYP1A1*2C). For the statistical analysis, the MINITAB 16.0 (Multiple Logistic Regression Test), SNPstats (Inheritance Model tests) and BioEstat 5.0 (Hardy-Weinberg test) tests were used. Results: Women with old age and the alcohol consumption had increased risk for developing breast cancer. Women with breast cancer had slightly higher frequency (51%) of the GSTM1 null genotype than women without cancer (49%), however this difference was not significant statistically. GSTT1 null genotype was also not associated with breast cancer. CYP1A1*2A polymorphism was associated with the risk for breast cancer and CYP1A1*2C polymorphism was more frequent in tumors with no distant metastases. Conclusions: Women with age advanced and who drink alcohol present increased risk for developing breast cancer. CYP1A1*2A polymorphism is associated with breast cancer and CYP1A1*2C polymorphism is related to women with no distant metastases. The polymorphisms of the GSTM1 and GSTT1 genes are not associated with the development of breast cancer.